The systematic registration of property law and cadastre on the territory in Romania: discussing a case study - Robert BANCIOIU; Leontina KOVACS (Nova Geodesia, 2022)
The systematic registration of real estate on the territory of a state represents the way to the rapid development of the market economy by reducing transaction costs, securing property rights, reducing or avoiding corruption and attracting investors. This work presents the way to create a systematic cadastre sector in the form of a case study, in accordance with the systematic cadastre procedures at the level of Romania, and its impact on sustainable development. In Romania, systematic registration is realised in the Eterra electronic database starting with the year 2015, together with the establishment of the National Agency for Cadastre and Land Registration (ANCPI) program 2015-2023. Registration is carried out exclusively at the level of the administrative-territorial unit (U.A.T.), respectively commune, city, municipality or at the level of one or more cadastral sectors, depending on the contract concluded between the executor and the local municipality. The procedures and stages of carrying out systematic cadastre works are regulated by Law number 7/1996 on cadastre and real estate advertising and the Regulation of July 9, 2014, on approval, reception and registration in the cadastre records and land register, as approved by the Order ANCPI number 700/2014. The financing of the program is made from three different sources: own revenues of the ANCPI in the amount of approximately 900 million euros, non-refundable external funds (European Union) in the amount of approximately 312 million euros, allocations from the budget of the units administrative-territorial through co-financing and is done free of charge for property owners.